Coming of Age and Urban Landscapes in Edward P. Jones’s “Spanish in the Morning” and “The Girl Who Raised Pigeons” - Lénárt-Muszka, Zsuzsanna (Hungarian Journal of English and American Studies, 2020)
This analysis of “Spanish in the Morning” (2009) and “The Girl Who Raised Pigeons” (1992) by Edward P. Jones offers a preliminary (re-)interpretation of the urban imaginary in Jones’s oeuvre by focusing on how urban places interact with the protagonists’ coming-of-age process. Detailed descriptions of routes, references to exact locations in the city, spatial relations, and changes of place run through both stories. Relying on trauma theory and Jon Anderson’s conceptualization of places, the essay argues that the geographical landscape is in the forefront in these narratives, but not as a means of emphasizing, matching, or complementing the emotional one, but rather to hide it from view. The protagonists’ memories and identities gain expression in spatial terms, but foregrounding the city is posited as a hindrance to their coming-of-age process insofar as it prevents them from accepting the reality of their loss and from facing and coping with trauma. (ZsLM)